PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, CORPORATE SOCIAL RESPONSIBILITY, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN - Bening Puspaningtyas; Eny Kusumawati (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze and determine the influence of profitability, liquidity, leverage, corporate social responsiveness, and managerial ownership on the Company's value. The data used in the study is secondary data sourced from the annual report of non-financial companies on the Indonesia Stock Exchange in 2019-2021. The sampling of this study was carried out by the purposive sampling method and 279 data were obtained. The results of the study provide empirical evidence that profitability and liquidity affect the value of the company, while leverage, corporate social responsiveness, and managerial ownership have no effect on the value of the company